Historicism of thinking and the concept of the epoch in Z. Tolgurov's novel "Blue Tipchak" - Аlena M. Sarbasheva; Asiyat D. Atabieva (Кавказология)
The article focuses on a comprehensive, conceptual analysis of the novel Z. Tolgurov’s “Blue Tipchak”, a holistic presentation of various semiotic levels of the work. The work determines conditionality of the epic beginning and the principles of implementing the author’s plan by the historicism of the writer’s thinking. Important in interpreting semantic perspectives of a literary text is the category of time. The dominant storylines are considered through the correlation of the destinies of the main characters with the dramatic nature of the depicted era of the 40-50s of the last century. The study emphasizes the multi-aspect nature of the problematic of the work (ideological, moral, psychological). In conjunction with the designated thematic blocks, the article explores the potential of the symbolic imagery of the novel. The idea of how the ideological situation can influence the fate of a person, cause internal transformations in him, followed by complete depersonalization, separation from ethnic roots (the image of the boy of the Crimea is indicative in this regard) acts as a nodal content line. The narrative space of the epic canvas contributes to the disclosure of a powerful mythological layer, realized through parallels with the animal world (for example, the images of the stallion Alakez and the wolf Gazhai). The ambiguous interpretation of the Soviet era is guessed in the meanings of the symbol displayed in the title of the work. The blue tipchak in the writer's interpretation personifies the deceptive appearance of communist ideology, implying the danger hidden in it. In the research's course, the multilevel nature of the novel context is revealed, because of the historical approach to understanding reality.